Options for Incorporating Energy Efficiency into Extension Programs: A Menu of Possibilities for Extension Energy Programming in Your Community - Lee Hayes Byron; Alane Humrich; Marianne Schmink; Jennison Kipp; Kimberly Davis; Paul Monaghan (EDIS)
This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication is part of a series showing how Extension agents, community activists and sustainability educators can implement a program that reduces energy use and saves money on utility expenses for low-income households. This document outlines a range of options for Extension agents to consider when planning to integrate energy education into their Extension programs. It provides initial steps that require little to no resources, as well as additional possibilities at medium to higher costs (both financially and in terms of staff time). https://edis.ifas.ufl.edu/wc409